The Importance and Some Problems of English Language Learning - sukirmiadi sukirmiadi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2015)
As one of the International languages, English is becoming more and more important in this globalization era. In Indonesia, this language is taught and learnt from Elementary school up to University level. This means that the learners (students) have studied it for more than 10 (ten) years but in fact most of them are not capable of producing the two language skills (speaking and writing) very well. This might happen to the two other skills, listening and reading. Based on the writer’s experience during his teaching, especially to non-English department students, he found that more than 90% of them, their English competence were very poor. This might be caused by some aspects, such as the inconsistency between the spelling and its pronunciation and many other patterns of grammatical structures that were much different from those of Indonesian language and even more complex and sophisticated as well. As a teacher, s/he has to know how to make those two problems simpler and easier to understand. Besides giving them many chances to practice the language being learnt more and more. Finally, it is expected that this method could make the students capable of catching the idea from the teacher easier to understand and make use of it very well in their real practice.